Pediatric Resident Knowledge, Confidence, and Experience in Transitioning Youth with Special Healthcare Needs - Weeks, Kerri; Harris, Kari; Bijjula, Ragneel R; Ahlers-Schmidt, Carolyn R (Kansas Journal of Medicine, 2014)
Background. The transition from pediatric to adult healthcare is vital to the 17% of adolescents with special healthcare needs (SHCN). Barriers to successful transition exist. The purpose of this study was to assess the baseline knowledge, confidence, and experience of pediatric residents in our state on transitioning adolescents with SHCN from pediatric to adult-oriented health care. Methods. An anonymous, voluntary, self-report survey was distributed electronically via Survey Monkey® to 2011-2012 pediatric residents in the state of Kansas (n = 39). Results. Of 39 pediatric residents, 21 (54%) completed the survey. Most (71%) had two or fewer adolescents with SHCN on their patient panel. Overall, the majority categorized their knowledge (71%) and experience (81%) transitioning adolescents with SHCN as minimal or very minimal. Conclusions. Pediatric residents report a general lack of knowledge, confidence, and experience in transitioning youth with SHCN. Additional training opportunities are needed to overcome the barriers in successful transition planning.